2013
DOI: 10.1021/nl402661p
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nanostructured Bilayer Solid Oxide Fuel Cell with 1.3 W/cm2 at 450 °C

Abstract: Obtaining high power density at low operating temperatures has been an ongoing challenge in solid oxide fuel cells (SOFC), which are efficient engines to generate electrical energy from fuels. Here we report successful demonstration of a thin-film three-dimensional (3-D) SOFC architecture achieving a peak power density of 1.3 W/cm(2) obtained at 450 °C. This is made possible by nanostructuring of the ultrathin (60 nm) electrolyte interposed with a nanogranular catalytic interlayer at the cathode/electrolyte in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 32 publications
3
154
0
Order By: Relevance
“…For that reason, studies on the fabrication of thin electrolytes have focused on yttria-stabilized zirconia, which has been widely used as an electrolyte material at high temperatures, rather than the ceria-based electrolytes [10][11][12][13] . When using the thin ceria-based electrolytes, buffer layers should be applied to protect the materials from reduction by preventing contact with the reducing gas 14,15 . The former often uses expensive deposition devices, such as pulsed laser deposition 12 that many researchers have chosen to prepare the thin film, and the latter requires complex cell fabrication processes and has the possibility of thermal expansion mismatch between the GDC and the buffer layers.…”
mentioning
confidence: 99%
“…For that reason, studies on the fabrication of thin electrolytes have focused on yttria-stabilized zirconia, which has been widely used as an electrolyte material at high temperatures, rather than the ceria-based electrolytes [10][11][12][13] . When using the thin ceria-based electrolytes, buffer layers should be applied to protect the materials from reduction by preventing contact with the reducing gas 14,15 . The former often uses expensive deposition devices, such as pulsed laser deposition 12 that many researchers have chosen to prepare the thin film, and the latter requires complex cell fabrication processes and has the possibility of thermal expansion mismatch between the GDC and the buffer layers.…”
mentioning
confidence: 99%
“…They achieved a maximum power density of 155 mW·cm -2 at 510 ºC using a membrane with an active area of 13.5 mm 2 . Another very interesting microfabrication approach is that suggested by An et al 15 , who in fact achieved the highest power output ever published on a µSOFC, 1.3 W·cm -2 . They enhanced the active area of the membrane by using a three-dimensional nanostructured membrane fabricated by means of nanosphere lithography (NSL) and atomic layer deposition (ALD).…”
Section: Micro Sofc Conceptmentioning
confidence: 99%
“…The complete reaction of such syngas flow would correspond to a fuel cell current of 0.85 A, thus around 0.5 W power generation. Considering present m-SOFC performance [52], this power is achieved with an active area of 0.5e1 cm 2 , thus about the footprint of our micro-reactor. Although other micro reactor studies demonstrated good yields of hydrogen at higher operation temperatures (>800 C) in tube-furnaces [10], our work demonstrated for the first time a ceramic micro-reactor that delivers syngas in a self sustained way with a sufficient output for a m-SOFC membrane with the same footprint.…”
Section: Thermally Self-sustaining Operationmentioning
confidence: 99%